THE RELEVANCE OF MEHDI HAIRI YAZDI'S EPISTIMOLOGY WITH THE TRADITION OF BOARDING-BASED HIGHER EDUCATION AT THE PESANTREN ZAINUL HASAN GENGGONG - Fatimah, Nur; Soleh, Achmad Khudori (UIN Antasari Banjarmasin, 2024)
Mehdi Hairi Yazdi is a prominent modern philosopher who sought to revive Islamic philosophy by integrating it with Western thought. Drawing on Suhrawardi’s philosophy of illumination, Mehdi explored its alignment with Western philosophical concepts. A key contribution of his thought to modern Islamic philosophy is the concept of Hudhuri science, an epistemology based on intuition and reason. This research examines the relevance of Mehdi’s epistemology to the Pesantren-based higher education tradition at Pesantren Zainul Hasan. Employing a qualitative method with content analysis, the study explores the relationship between Mehdi’s epistemology and the Pesantren’s educational practices. Findings indicate that the Pesantren Zainul Hasan tradition emphasizes critical reasoning, religious practices, and the pursuit of spiritual blessings, forming the foundation of its higher education epistemology. Both the Pesantren’s approach and Hudhuri epistemology share commonalities in acquiring knowledge through Sufistic and rational paths.